Individual localization value of resting-state fMRI in epilepsy presurgical evaluation: A combined study with stereo-EEG. Issue 12 (December 2021) - Tang, Yingying; Choi, Joon Yul; Alexopoulos, Andreas; Murakami, Hiroatsu; Daifu-Kobayashi, Masako; Zhou, Qin; Najm, Imad; Jones, Stephen E; Wang, Zhong Irene
Highlights: First study to examine the localization value of resting-state fMRI metrics for seizure onset zone (SOZ) defined by SEEG at the individual level. Amplitude of low-frequency fluctuations (ALFF) demonstrated concordant clusters with SEEG-defined SOZ in 73.7% of patients. All concordant clusters showed regional activation, representing increased neural activities. Results suggest ALFF activation on resting-state fMRI can add localization information for SOZ for individuals with intractable focal epilepsies. Abstract: Objective: To examine the individual-patient-level localization value of resting-state functional MRI (rsfMRI) metrics for the seizure onset zone (SOZ) defined by stereo-electroencephalography (SEEG) in patients with medically intractable focal epilepsies. Methods: We retrospectively included 19 patients who underwent SEEG implantation for epilepsy presurgical evaluation. Voxel-wise whole-brain analysis was performed on 3.0 T rsfMRI to generate clusters for amplitude of low-frequency fluctuations (ALFF), regional homogeneity (ReHo) and degree centrality (DC), which were co-registered with the SEEG-defined SOZ to evaluate their spatial overlap. Subgroup and correlation analyses were conducted for various clinical characteristics. Results: ALFF demonstrated concordant clusters with SEEG-defined SOZ in 73.7% of patients, with 93.3% sensitivity and 77.8% PPV. The concordance rate showed no significant difference when subgrouped by lesional/non-lesional MRI, SOZ location, interictal epileptiform discharges on scalp EEG, pathology or seizure outcomes. No significant correlation was seen between ALFF concordance rate and epilepsy duration, seizure-onset age, seizure frequency or number of antiseizure medications. ReHo and DC did not achieve favorable concordance results (10.5% and 15.8%, respectively). All concordant clusters showed regional activation, representing increased neural activities. Conclusion: ALFF had high concordance rate with SEEG-defined SOZ at individual-patient level. Significance: ALFF activation on rsfMRI can add localizing information for the noninvasive presurgical workup of intractable focal epilepsies.